Syakhshiyât Al-Mudarris - Harapandi Dahri (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Being a al-mudarris is a very glorious job as he or she conveys, guides and makes human has more meaning in his life. Al-Mudarris including teachers, not just for himself or herself, but also for others. In addition, al-mudarris will be a guide in carrying out a full life value. Speech, actions, attitudes and behaviors will be the reference of all people, especially the students and the surrounding community, that’s why al-mudarris are expected to always maintain his attitude, speech and behavior weather he is giving a lecture or when he is not giving a lecture.